Agriculture in al-Hamdānī's Yemen: A Survey from Early Islamic Geographical Texts - Varisco, Daniel Martin (Journal of the economic and social history of the Orient, 2009)
Abstract The area of Yemen has been one of the most productive agricultural regions in the Arab World since the beginning of Islam. This article surveys the available knowledge from Arabic geographical and historical texts on the state of agriculture in Yemen during the early Islamic period up through the 10th century CE. The primary focus is on the work of Abū Muhammad al-Hasan al-Hamdānī, including translation of a section on Yemeni agriculture from his Sifat jazīrat al-Arab. In addition to discussion of rain periods, water resources and agricultural methods, information on the known cultivated crops is provided. Depuis le commencement de l'ère islamique le Yémen constitue la région agricole la plus fertile du monde arabe. Cette contribution étudie l'agriculture au Yémen jusqu'au Xe siècle EC en exploitant les textes géographes et historiques arabes disponibles, tout d'abord les écrits de Abū Muhammad al-Hasan al-Hamdānī, y inclut la traduction de la section qui traite de l'agriculture yéménite de son Sifat jazīrat al-Arab.Des considérations sur les pluies saisonnières, les ressources d'eau douce, et la méthode de culture, l'étude nous révèle en outre des détails sur la nature des produits agricoles connus.